Conceptualizing sexual orientation as a “suspect” category in non-discrimination law: Some reflections on the atala judgment of the inter-american court of human rights - Loenen, Titia (Derecho y Humanidades, 2014)
The judgment of the Inter-American Court of Human Rights in the case of Atala Riffo and daughters v. Chile of 24 February 2012 considers that sexual orientation is included in the protection provided by the right to equality and non-discrimination in the American Convention on Human Rights. In this contribution I will reflect on the conceptualization of sexual orientation as a “suspect” category in non-discrimination law and its implications. To do so, I will first address the core meaning and purpose of the right to equality and non-discrimination and the importance of the distinction to be made between “suspect” and “non-suspect” classifications or distinctions (section 2). The next section will explore the question how to draw the line between “suspect” and “non-suspect” classifications. What are the underlying foundations for approaching a ground of classification as suspect and how do these relate to approaching sexual orientation as a suspect ground (section 3)? I will conclude by returning to the Atala judgment and trying to answer the question how and to what extent this conceptual analysis is reflected in the Court’s considerations (section 4).